Symposium 1: Why Did It Work For Us? : Reflections on a successful networked learning community - Groves, Karen; Etherington, Clare; Cochrane, Jill; Moss, Bridget (Proceedings of the International Conference on Networked Learning, 2008)
This paper, written by a collective of eleven participants of one module of the MA in Clinical Education at Edge Hill University, attempts to capture the ongoing debate about the reasons for the "success" of this specific networked learning community. The 15 week blended learning module using WebCT, entitled "Designing and Tutoring E-learning Opportunities" concluded in June 2007. Most research into student engagement has been utilitarian and has not explored the characteristics which underpin the concept of engagement and others have relied on the methodology of using "before and after" questionnaires to try to tease out student expectations and experiences. In contrast, this paper is centred on participants' experiences, indeed it is written by participants, thus giving a different research perspective on networked learning communities. It was a general feeling within the group of this being a very successful, active, supportive and enjoyable learning experience and community, which prompted us to try to identify the characteristics of the experience which marked it out from other experiences we have had of online learning. Method The participants met to discuss the course and agreed to share the work of analysis. Two participants undertook a quantitative and a qualitative analysis of the archived interactions on the WebCT discussion board and another compared the quantitative data with data available from the previous occasion on which the same module was delivered two years earlier. With the consent of all the course participants, we shared and, two participants, analysed qualitatively, reflective statements upon our own contributions to the discussion board, submitted confidentially as part of the module assessment. A thematic analysis of this post course meeting was undertaken by one participant. Results The success of the group appeared to be linked to membership from a variety of backgrounds, with differing learning styles, given well-designed activities in which to participate. The enthusiasm for the subject and course was high and maintained by great peer support. All participants were highly motivated and appeared to have a reasonable amount of regular time to devote. The level of discussion was high promoting a real sense of camaraderie, bonding and shared learning in a relaxed atmosphere. The participants brought with them a degree of sophistication of e-discussion from previous modules/courses and naturally fell into various roles in the group but were flexible and able to take on other roles when needed. There were many peer facilitators. This module provided a circular process, with technology as both the medium and the end. The resulting was a demystifying of e-learning which immersion and transformation resulted in achievement of deep learning. Increasingly, as participants felt able to contribute for discussion sake and not just for assignments, activities felt less task orientated. They became more conscious of the impact of their contributions, making more effort to have predictable effects with them; attempting to limit their own damaging behaviours; and were prompted to be more rounded contributors in discussions, responding specifically to the contributions of others and trying to encourage participation from the less vocal. The module had a sense of group enjoyment and humour, lots of fun and laughter, a sense of mutual respect and democracy, good listening and consequent relatedness of discourse, without strident or disruptive exchanges and the ever evident tutor role as non directive facilitators. For some it was only by doing it themselves within the module that the understanding of the module, and the added value of e-learning, could be realised.